2022
DOI: 10.1177/19418744221123208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Diagnostic Frequency of Febrile Seizures: An Electronic Health Record Database Observational Study

Abstract: Background and Purpose Febrile seizures are common in children and are associated with viral infection. Mitigation strategies implemented during the coronavirus disease 2019 (COVID-19) pandemic have slowed the spread of all viral illnesses potentially impacting febrile seizure frequency. The objective of this study is to assess the impact of COVID-19 mitigation strategies on the diagnostic frequency of febrile seizures. Methods This was a retrospective observational cohort study utilizing TriNetX ® electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Data privacy, security, attestation, and steps taken to ensure de-identification have been previously described. 12,13…”
Section: Methodsmentioning
confidence: 99%
“…Data privacy, security, attestation, and steps taken to ensure de-identification have been previously described. 12,13…”
Section: Methodsmentioning
confidence: 99%
“…Although the incidence of seizures in children with fever during the COVID-19 pandemic has significantly increased ( Iijima et al, 2022 ; Joung et al, 2023 ), in the latest retrospective case-control study, the risk of FSs secondary to COVID-19 did not increase compared to other causes ( Hanlon et al, 2023 ). Meanwhile, a retrospective observational cohort study showed an increased frequency of complex FSs diagnoses during the COVID-19 pandemic ( Cadet et al, 2023 ). Further analysis of the clinical features of FSs in patients with and without COVID-19 revealed that patients with FSs in COVID-19 tended to be predominantly male and had a later age of onset compared with non-Covid-19 patients ( Seo et al, 2023 ).…”
Section: Introduction Of Febrile Seizuresmentioning
confidence: 99%